Wide Band Flexible Antenna For Future V2X And 5G Automotive Vehicular Imaging And Position Prediction Applications - Reddy, Y. V. Bhaskar; Prasad, A. Mallikarjuna; Swamy, K. Veera (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In this work monopole automotive antenna is designed and analysed using ANSYS HFSS. Polyamide material is take as the substrate material having dielectric constant of 2.9.The antenna is enclosed in an automotive application scenario where the antenna shows its peak performance involving in the occurrence of 3.5GHz(WiMAX) and 5.8(WLAN) and Vehicular communication bands. The proposed antenna works at modern commercial applications and it also verified on virtual automotive scenario. The antenna gets a maximum gain of 4.8dB and average gain of 3.2Db.The proposed antenna exhibits stable type of performance in and out automotive scenario having gain of above 3Db.The antenna is getting radiation efficiency of 90 percent and having front to back ratio of above 75 percent in peak maximum scenario.